2022
DOI: 10.31557/apjcp.2022.23.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Chemotherapy Induced Adverse Events in Pediatric Osteosarcoma Patients

Abstract: Objective: To investigate the prevalence of chemotherapy-induced adverse events and the associated risk factors in pediatric patients with osteosarcoma. Methods: This retrospective cross-sectional study enrolled 90 pediatric osteosarcoma patients (with 1,017 chemotherapy cycles) treated at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Chemotherapy-induced unfavorable occurrences can exert a noteworthy influence on the quality of life of individuals afflicted with osteosarcoma. Negative occurrences such as nausea and vomiting, hepatotoxicity, anemia, neutropenia, and thrombocytopenia were discovered to be widespread in pediatric osteosarcoma patients enduring chemotherapy [13]. Factors linked with chemotherapy-induced liver toxicity comprised of increased chemotherapy quantities, elevated plasma methotrexate levels, and a more gradual pre-hydration velocity [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy-induced unfavorable occurrences can exert a noteworthy influence on the quality of life of individuals afflicted with osteosarcoma. Negative occurrences such as nausea and vomiting, hepatotoxicity, anemia, neutropenia, and thrombocytopenia were discovered to be widespread in pediatric osteosarcoma patients enduring chemotherapy [13]. Factors linked with chemotherapy-induced liver toxicity comprised of increased chemotherapy quantities, elevated plasma methotrexate levels, and a more gradual pre-hydration velocity [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to decide which is superior amidst these combinations while multiple studies revealed different efficacy outcomes. Additionally, multi-drug chemotherapy toxicity could affect the patients quality of life [13]. Hereby, we carried out a meta-analysis approach to assess the efficacy and safety of a specific combination of MAP regimen compared to other regimens as chemotherapy protocols for the treatment of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Myelosuppression is a common potentially life‐threatening adverse effect (AE) of chemotherapy in childhood cancers 1 . Chemotherapy‐induced neutropenia (CIN) is dose‐dependent and occurs in 26%–45% of treated individuals 2,3 . CIN is associated with high morbidity and mortality in children 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Chemotherapy‐induced neutropenia (CIN) is dose‐dependent and occurs in 26%–45% of treated individuals. 2 , 3 CIN is associated with high morbidity and mortality in children. 3 Moreover, CIN can lead to chemotherapy interruption and dose adjustments, affecting the treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%